1997
DOI: 10.1007/s007050050117
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco veinal necrosis determinants are unlikely to be located within the 5′ and 3′ terminal sequences of the potato virus Y genome

Abstract: Three potato virus Y isolates, representatives of distinct PVY groups, identified in potato fields in northern Poland were submitted to biological and molecular analysis. Phenotypically, two isolates, PVYN-Ny and PVYN-Wi, belong to the necrotic strain and the third one (PVYO-LW) to the common strain. PVYN-Wi, however, did not react with monoclonal antibodies directed against the necrotic strain isolates which recognise PVYN-Ny. To characterise the isolates, coat protein genes were sequenced and compared with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…Therefore, classification of potato isolates of PVY based on the 3 0 -UTR implies that this region cannot be used to demarcate strains of the isolates. Furthermore, it seems the unique 3 0 -UTR sequence of PVY is not related to the tuber or tobacco leaf necrosis symptoms, as also indicated by others [7,25]. One would expect there to be some level of correlation between the serology assays and CP sequences of PVY since the MAbs bind to the CP, however, as we have demonstrated in this paper, there is no direct correlation.…”
Section: Strain Demarcationmentioning
confidence: 48%
See 3 more Smart Citations
“…Therefore, classification of potato isolates of PVY based on the 3 0 -UTR implies that this region cannot be used to demarcate strains of the isolates. Furthermore, it seems the unique 3 0 -UTR sequence of PVY is not related to the tuber or tobacco leaf necrosis symptoms, as also indicated by others [7,25]. One would expect there to be some level of correlation between the serology assays and CP sequences of PVY since the MAbs bind to the CP, however, as we have demonstrated in this paper, there is no direct correlation.…”
Section: Strain Demarcationmentioning
confidence: 48%
“…3, 4). Chachulska et al [7] also found high nucleotide homology (99-100%) between serology determined O-and N-strains in the 3 0 -UTR. Therefore, classification of potato isolates of PVY based on the 3 0 -UTR implies that this region cannot be used to demarcate strains of the isolates.…”
Section: Strain Demarcationmentioning
confidence: 85%
See 2 more Smart Citations
“…Alignments were performed using the ALIGN program version 2.0, available on the INFOBIOGEN internet site (Myers & Miller 1989). Six PVY isolates representing O and N groups [used for phylogenetic studies by Revers et al (1996) and Chachulska et al(1997)] and two strains that have been completely sequenced, PVY-Canada (O) (Singh & Singh, 1996) and PVY-N605 (N) (Jakab et al 1997), were used in this analysis.…”
Section: Sequence Analysismentioning
confidence: 99%